The Effect of Cooperative Learning Group Investigation Type In Science With an Outdoor Learning System Approach on Problem Solving Skills and the Mastery of Concepts in Junior High School Student - Fitri Nur Aini (Journal of Science Education Research, 2020)
The research aimed to know (1) the effect of the implementation cooperative learning group investigation type with an outdoor learning system on problem-solving skills, (2) the effect of the implementation cooperative learning group investigation type with an outdoor learning system on the mastery of concepts, and (3) the simultaneous effect of cooperative learning group investigation type with an outdoor learning system on problem-solving skills and the mastery of concepts. This research was a quasi-experimental research with a nonequivalent pretest-posttest control group design. The population was the seventh-grade students of SMP N 2 Tempel. The sample selection technique used the purposive sampling technique; class of VIII C played as an experimental class and VIII D played as control class. The instruments on data collection used problem-solving tests and mastery of concept tests. The parametric test used in this research which was an independent sample t-test followed by effect size, and MANOVA. The results showed: (1) there was an effect of the implementation cooperative learning group investigation type with an outdoor learning system on problem-solving skills with poor category, (2) there was an effect of the implementation cooperative learning group investigation type with an outdoor learning system on the mastery of concepts with high effects, and (3) there was a simultaneous effect of cooperative learning group investigation type with an outdoor learning system on problem-solving skills and the mastery of concepts.